2007
DOI: 10.2471/blt.06.036962
|View full text |Cite
|
Sign up to set email alerts
|

Health and foreign policy: influences of migration and population mobility

Abstract: International interest in the relationship between globalization and health is growing, and this relationship is increasingly figuring in foreign policy discussions. Although many globalizing processes are known to affect health, migration stands out as an integral part of globalization, and links between migration and health are well documented. Numerous historical interconnections exist between population mobility and global public health, but since the 1990s new attention to emerging and re-emerging infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
49
0
14

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 10 publications
(7 reference statements)
0
49
0
14
Order By: Relevance
“…Driven by globalisation, tourism, migration, conflict and labour markets, international mobility presents risks for HIV transmission [1][2][3]. Acquisition of HIV via cross border travel has been an increasing proportion of diagnoses for high income countries, changing patterns of epidemics [4].…”
Section: Introductionmentioning
confidence: 99%
“…Driven by globalisation, tourism, migration, conflict and labour markets, international mobility presents risks for HIV transmission [1][2][3]. Acquisition of HIV via cross border travel has been an increasing proportion of diagnoses for high income countries, changing patterns of epidemics [4].…”
Section: Introductionmentioning
confidence: 99%
“…2 The 2009 United Nations Human Development Report 3 suggested that migration benefits people who move, through increased economic and education opportunities, but migrants frequently face barriers to local health and social services. In Canada, international migrants are a growing 4 and economically important segment of the population (Table 1A).…”
mentioning
confidence: 99%
“…Migration often increases vulnerability to HIV infection (Decosas, Kane, Anarfi, Sodji, & Wagner, 1995;MacPherson, Gushulak, & Macdonald, 2007;Quinn, 1994). This phenomenon has been well described for populations of women migrants in a diversity of situations (Webber, 2007), and for rural-to-urban migrants of both genders in China (Hong et al, 2006;Hu, Liu, Li, Stanton, & Chen, 2006;Yang, Derlega, & Luo, 2007).…”
Section: Context Of Migration and The Hiv Epidemic In Cambodiamentioning
confidence: 93%